PENGARUH GLOBAL TOURISM TERHADAP PERUBAHAN NILAI LOKAL MELALUI LEGALISASI ALKOHOL DI UNI EMIRAT ARAB - Putra, Alfen Redho (Prodi Ilmu Hubungan Internasional, Universitas Fajar, 2024)
This article examines how changes in local norms resulting from the legalization of alcoholic beverages, which were previously strictly prohibited and even classified as activities considered serious crimes in the country, are assumed to have changed into social values in life. In analyzing this incident, the author uses the perspectives of three experts, including Mac Kercher, who considers this phenomenon as a way of thinking. He argues that the existing international community will potentially influence the culture of life of local communities in the country. The author then uses the concept of national interest and mercantilism as additional approaches. In this case, the author shows that changes in local norms due to the legalization of alcoholic beverages are driven by four national ambitions. namely increasing the number of tourists to increase global tourism potential and meet the needs of the majority. The number of global tourists coming mainly from Western countries, namely the European region where alcohol consumption is very high, especially Western Europe, as well as the need for efforts to transition the economic pillars and the benefits of the name change plan. namely from oil and gas countries to non- oil and gas countries, especially in the tourism sector. Finally, the recovery of the economy which has been in crisis for a year due to the corona virus pandemic. Keywords: Global Tourism, Local Norms, Alcohol, United Arab Emirates, Legalization